Determinants of the Effectiveness of Corporate Codes of Ethics: An Empirical Study - Singh, Jang B. (2011)
Recent figures reported by KPMG confirm the growing prevalence of corporate codes of ethics globally. Svensson et al. (Bus Ethics 18:389–407, 2009) in surveys of the largest corporations in Australia, Canada, and Sweden found a similar trend. The increased prevalence of corporate codes of ethics has been accompanied by heightened research interest in various aspects of these documents, e.g., the contents and focus of the codes. However, there is a paucity of research examining the effectiveness of these documents and the organizational infrastructure that accompany them. This study, based on a survey of Canada’s largest corporations, sought to empirically assess the determinants of the effectiveness of corporate codes of ethics by regressing managers’ perceptions of code effectiveness against various elements of ethics programs. It was found that, in a statistically significant model, eighteen independent variables explain 58.5% of the variance in the perceived effectiveness of corporate codes of ethics.
Keywords: determinants of code effectiveness; corporate codes of ethics; effectiveness of codes